Released washed platelet concentrates are effective and safe in patients with a history of transfusion reactions. Issue 6 (December 2018) - Fujiwara, Shin-ichiro; Fujishima, Naohito; Kanamori, Heiwa; Ito, Masumi; Sugimoto, Tatsuya; Saito, Shoko; Sakaguchi, Takeshi; Nagai, Koichi; Masuoka, Hidekazu; Nagai, Kazuhiro; Morita, Akie; Kino, Shuichi; et al.
Abstract: Background: Plasma removal by washing is an effective approach to prevent transfusion reactions by platelet concentrates (PCs). Recently, washed PCs were released by the Japanese Red Cross Society (JRCS). Materials and methods: This retrospective multicenter study evaluated the efficacy and safety of released washed PCs (RWPCs) between September 2016 and January 2017 in Japan. The RWPCs were prepared by washing leukoreduced apheresis PCs with the platelet additive solution, BRS-A, using automated cell processors. Results: Clinical data were obtained from 91 patients and 1210 RWPC transfusions at 50 institutions. The median number of RWPC transfusions per patient was 8 (range, 1–91). RWPCs were used in 94.5% of the patients with a history of recurrent or severe transfusion reactions for preventing such reactions. Responses of RWPCs were evaluated as complete response (91.6%), partial response (8.2%), no-change (0.2%), and progression (0%) and overall response was equal across subgroups divided by patients' profiles. The median corrected count increment (CCI) at 1 and 24 h post-transfusion were 13.5 (range, 1.9–35.4) × 10 9 /L and 3.5 (range, −13 to 53.6) × 10 9 /L, respectively, and median CCI at 24 h was 5.5 (range, −13 to 53.6) × 10 9 /L in patients without risk factors associated with platelet transfusion refractoriness. Transfusion reactions to RWPCs were observed in only nine transfusions (0.7%), all of which were mild allergic reactions. Conclusion: This study demonstrated that RWPCs were effective and safe in patients with a history of transfusion reactions. Further prospective studies on efficacy together with cost-benefit analysis in RWPCs are needed.